Maternal Employment Effects of Paid Parental Leave - Annette Bergemann; Regina T. Riphahn (Institute for the Study of Labor (IZA), 2015)
We study the short, medium, and longer run employment effects of a substantial change in the parental leave benefit program in Germany. In 2007, a means-tested parental leave transfer program that had paid benefits for up to two years was replaced by an earnings related transfer which paid benefits for up to one year. The reform generated winners and losers with heterogeneous response incentives. We find that the reform speeds up the labor market return of both groups of mothers after benefit expiration. The overall time until an average mother with (without) prior claims to benefits returns to the labor force after a birth declined after the reform by 10 (8) months at the median. We show that likely pathways for this substantial reform effect are changes in social norms and mothers' preferences for economic independence.
Keywords: J13; J21; 330; female labor supply; maternal labor supply; parental leave; parental leave benefit; child-rearing benefit; parents' money